When One Health Meets the United Nations Ocean Decade: Global Agendas as a Pathway to Promote Collaborative Interdisciplinary Research on Human-Nature Relationships - Masterson-Algar, Patricia; Jenkins, Stuart R.; Windle, Gill; Morris-Webb, Elisabeth; Takahashi, Camila K.; Burke, Trys; Rosa, Isabel; Martinez, Aline S.; Torres-Mattos, Emanuela B.; Taddei, Renzo; Morrison, Val; Kasten, Paula; et al. (Frontiers in Psychology, 2022)
Strong evidence shows that exposure and engagement with the natural world not only improves human wellbeing but can also help promote environmentally-friendly behaviours. Human-nature relationships are at the heart of global agendas promoted by international organizations including the World Health Organization’s (WHO) ‘One Health’ and the United Nations (UN) ‘Ocean Decade’. These agendas demand collaborative multisector interdisciplinary efforts at local, national and global levels. However, while global agendas highlight global goals for a sustainable world, developing science that directly addresses these agendas from design through to delivery and outputs does not come without its challenges. In this article we present the outcomes of international meetings between researchers, stakeholders and policymakers from the United Kingdom and Brazil. We propose a model for interdisciplinary work under such global agendas, particularly the interface between One Health and the UN Ocean Decade and identify three priority research areas closely linked to each other: human-nature connection, conservation-human behaviour and implementation strategies (bringing stakeholders together). We also discuss a number of recommendations for moving forward.